Balance of Payments Constrained Growth Model: The Case of India - Arslan Razmi (University of Massachusetts, Department of Economics, 2005)
This study applies the Balance of Payments Constrained Growth (BPCG) model to India, a large developing country with a relatively low trade to GDP ratio. Rather than assuming similar elasticities of substitution between goods produced in different regions, the study extends the model to relax these assumptions. Johansens cointegration technique is employed to estimate trade parameters. Short-run adjustments are explored within a vector error correction framework. The average growth rates predicted by various forms of the BPCG hypothesis are found to be close to the actual average growth rate over the period 1950-1999, although individual decades display substantial deviations. JEL Categories: F43, F14, E12
Keywords: 330; Balance of payments-related constraints; real exchange rates; Johansens cointegration technique; strong form; weak form; trade multiplier; import compression